"GREEN INSURANCE" IN UZBEKISTAN: STATUS AND WAYS OF DEVELOPMENT (Лучшие интеллектуальные исследования, 2025)
Abstract: The article examines the importance and relevance of green insurance. The problems of implementing a green insurance system in Uzbekistan are studied, and proposals and recommendations for developing a green insurance system based on modern international criteria are formulated.